Pengaruh Metode Drill terhadap Hasil Belajar Matematika Siswa Kelas IV SDN Curug Wetan II - Muharram, Rizsaldy Chahya; Amaliyah, Aam; Rini, Candra Puspita (Lembaga Yasin AlSys, 2022)
This research is to find out the effect of drill methods on study mathematics results for IV grade student SDN Curug Wetan II. This research using experimental quasi research methods with research design Neonequivalent Control Group design. The population subject in this research its all students of IV grade SDN Curug Wetan II who have 58 students, with take a sample from two class who have 58 student from class IV A who have 30 students as a control class and class IV B who have 28 students as Experimental class. Data collection techniques using test question instruments, consisting of 14 valid and reliable questions. For test the hypothesis pretest In this study is using t-test, from the t-test results obtained calculated = -2.46 and table = 2.00, it can be concluded that there is no significant effect between the mean pretest scores of the control class and the experimental class. Meanwhile, for testing the posttest hypothesis, the t-test results obtained calculated = 8.52 and table = 2.00, it can be concluded that there is a significant effect between the average post-test scores of the control class and the experimental class. This can be interpreted that the results of learning mathematics IV grade students with using the drill method is higher than using the conventional learning method.